Implementasi Model PjBL terhadap Peningkatan Keterampilan Proses Sains dan Sikap Ilmiah Siswa Kelas VIII SMP - Anthony Firdaus; Yula Miranda; Soaloon Sinaga (Journal of Environment and Management, 2020)
It has been observed that the level of science process skills and students' scientific attitudes, to seome extent, has not been formed, so the learning activity process has been running in slow motion. This study aims to examine the impact of project based learning (PjBL model) on the improvement of students‘ science process skills (KPS) and scientific attitudes, especially on plant tissue lesson. A pretest-posttest research design was applied to two classes of 8th grade students of SMPN 9 Palangka Raya, namely class VIIIA as the treated group, and while VIIIb as the control class using conventional learning models. The instruments used were lesson plans, science process skills observation sheets, scientific attitude questionnaires, and a number of test questions for testing. The results show that PjBL can improve science process skills with an N-gain of 0.70 in treated group, which is classified as high category, and N-gain of 0.48 in the control class which is in the moderate category. The PjBL implementation does not improve scientific attitudes because the N-gain value is 0.58 in the experimental class, quite similar to 0.32 point in the control class; both fall on moderate category.